Measuring Future Perspective: Consideration of Future Consequences Scale Revalidation - Senyk, Oksana; Polunin, Oleksiy; Shatilova, Oleksandra; Abramov, Volodymyr; Kryvenko, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
Present behavior is influenced by its imaginary future consequences. However, it is known that the immediate and long-term consequences of the same behavior may have different effects on a person's well-being. Hence, when analyzing one’s way of making decisions, it is important to take into account how far-reaching consequences of their behavior are considered. Among the variety of methods to measure future time perspective and its motivational impact on one’s decisions and behavior, special attention should be paid to the Consideration of Future Consequences Scale (CFC), which consists of two sub-scales – immediate future and distant future. The scale allows to assess how far-reaching consequences of one’s own actions are taken into consideration when making decisions and acting in the present moment. The first adaptation of the scale into Ukrainian language was conducted in 2017 (Senyk, Riznyk, Horbal), which resulted in good reliability and validity scores for both subscales. However, the question of the possibility of using the Ukrainian version of the CFC as a unidimensional scale remained open. The present article is dedicated to reviewing the validity and reliability of the Ukrainian CFC in its one- and two-factor solutions. The sample comprised of 1137 participants (M = 21.05), residents of almost all Ukrainian regions and the Autonomous Republic of Crimea. The results have shown that the Ukrainian version of CFC has good validity and reliability in both two- and one-factor solutions, and therefore is recommended to be used for future research and in the field of individual practice.
Keywords: CFC-14; Consideration of future consequences scale; test adaptation